Ca2+‐Cl− Association in Water Revisited: the Role of Cation Hydration. Issue 19 (8th June 2017) - Salanne, Mathieu; Tazi, Sami; Vuilleumier, Rodolphe; Rotenberg, Benjamin
Abstract: We investigate the dissociation of a Ca 2+ ‐Cl − pair in water using classical molecular dynamics simulations with a polarizable interaction potential, parameterized from ab initio calculations. By computing the potential of mean force as a function not only of the interionic distance but also of the coordination numbers by water molecules, we show that it is necessary to use a collective variable describing the cation hydration in order to capture the dissociation mechanism. In the contact ion pair, the Ca 2+ cation has a first coordination sphere containing 5 or 6 water molecules. The minimum free‐energy path for dissociation involves a two‐step process: First one or two additional water molecules enter the cation coordination shell, increasing the coordination number up to 7 with an almost fixed interionic distance. Then the dissociation of the ionic pair occurs at this fixed coordination number. Abstract : What goes around : The dissociation of a calcium‐chloride ion pair in water (see Figure) involves rearrangements of the solvation shell of both ions. Using molecular simulations, we show that the coordination number of calcium by water molecules should be considered in addition to the interionic distance to investigate this process, in particular when computing the potential of mean force.